Early Allograft Dysfunction and Complications in DCD Liver Transplantation: Expert Consensus Statements From the International Liver Transplantation Society. Issue 8 (August 2021) - Quintini, Cristiano; Muiesan, Paolo; Detry, Olivier; Gastaca, Mikel; de Jonge, Jeroen; Clavien, Pierre-Alain; Del Prete, Luca; Fondevila, Constantino
Abstract : Livers for transplantation from donation after circulatory death donors are relatively more prone to early and ongoing alterations in graft function that might ultimately lead to graft loss and even patient death. In consideration of this fact, this working group of the International Liver Transplantation Society has performed a critical evaluation of the medical literature to create a set of statements regarding the assessment of early allograft function/dysfunction and complications arising in the setting of donation after circulatory death liver transplantation.